Factors associated with frailty syndrome in the rural elderly - Patrícia Mirapalheta Pereira de Llano; Celmira Lange; Carlos Alberto da Cruz Sequeira; Vanda Maria da Rosa Jardim; Denise Somavila Przylynski Castro; Fernanda Santos
ABSTRACT Objective: determine the prevalence and factors associated with frailty syndrome (FS) in the elderly in the rural population of Pelotas. Method: Quantitative, analytical, transversal study conducted with 820 elderly subjects registered in the Family Health Strategy (FHS) in the rural area in the municipality of Pelotas, from July to October 2014. Results: among those evaluated, 43.41% showed FS. These factors were consolidated as associated with the condition: low income (PR: 1.54, p ≤ 0.001), low educ. level (PR: 1.45, p ≤ 0.001), nutritional status (obesity) (PR:1.89, p ≤ 0.001), physical inactivity (PR:1.93, p = 0.003), cognitive deficit (PR:2.07, p = 0.005), and poor self-perceived health (PR: 8.21, p ≤ 0.001). Conclusion: the findings may contribute effectively to the establishment of prevention and screening measures for frailty among the elderly by health professionals, especially nurses, aiming to prevent the occurrence of the syndrome and adverse and undesirable outcomes.